“Dakwah Pembebasan” Perspektif KH. MA. Sahal Mahfudh Dalam Buku “Nuansa Fiqih Sosial” - Muhammad Ahnu Idris; Taufik Taufik; Bahrur Rosi (Ulumuna: Jurnal Studi Keilsman, 2020)
This article discusses the thoughts of da'wah bi al-hâl KH. MA Sahal Mahfudh in his book entitled "Shades of Social Fiqh".The research in this article is the reasech library with a qualitative descriptive approach. That is, the results of this paper are presented in the form of a translation based on the existing literature and data.Da'wah aims to bring mad'u achieve happiness in the world and the hereafter, therefore preaching is not merely a matter of the preacher who stands on the pulpit and conveys the hadith or verses of the Koran to mad'u. Empowering and freeing people from all forms of adversity, according to KH. MA Sahal Mahfudh, also included preaching. This method of preaching is called real action propaganda (da'wah liberation) or da'wah bi al-hāl or da'wah bi lisân al-hâl.This method of da'wah becomes very important, because when your physical needs are met, the messages of da'wah will be easily conveyed and accepted by mad'u thus, the purpose of da'wah will also be easily achieved. On the other hand, if people live in misery, then mad'u has the potential to deny the teachings of God.